Formation of Student Character Values Through Extracurricular Activities in Pondok Al-Islam Joresan Ponorogo - Ahmad Hidayatullah Zarkasyi; Nurul Azizah; Aksani Taqwim (Educan : Jurnal Pendidikan Islam, 2020)
At present in the life of the nation and state increasingly experiencing mental crises, morals, and behavior such as brawl problems, student fights that have been entrenched, corruption that has become a tradition, using drugs or liquor. This study aims to find out 1). the formation of student character values through extracurricular activities, 2). Factors that support and inhibit the formation of student character values through extracurricular activities in pondok al-Islam and 3. character values formed through extracurricular activities. This research is a descriptive qualitative research. Documentation is used to schedule extracurricular activities, the number of students participating in extracurricular activities and the name of the supervising teacher. While the technique of analyzing researchers data uses miles and huberman model analysis, namely data reduction, presentation and conclusion drawing. Checking the validity of the data using triangulation. the results of research at Pondok Al-Islam joresan showed that the formation of student character values through extracurricular activities at Pondok Al-Islam had a strategy, the strategies used were habituation and exemplaryness. 1). Habituation Strategy in the form of the first policy of the lodge in designing mandatory and optional extracurricular activities. Secondly, there are regulations to create discipline in carrying out extracurricular activities. 2). The first exemplary strategy is the example of the supervising teacher. The two officials are opmi. while supporting factors for the formation of student character values through extracurricular activities in Pondok Al-Islam, namely: 1). school policies in extracurricular implementation, 2). guidebook for student activities, 3). availability of competent supervisors. 4). family support or student guardian. The inhibiting factors are 1). the facilities and infrastructure of extracurricular activities are not yet complete. 2). lack of extracurricular tutor teacher. 3). Character values that are formed through extracurricular dipondok al-Islam, namely: Religious characters, Honest, Tolerance, Discipline, Hard Work, Creative, Independent, Curiosity, Friendly/Communicative, Peaceful Love, Social Concern and Social Responsibility.